Renal effects of dapagliflozin in patients with type 2 diabetes. (June 2014) - Thomas, Merlin C.
Diabetes mellitus was originally conceived as a renal disorder. In the last decade, however, there has been renewed interest in role of the kidney in the development and maintenance of high glucose levels. This has led to the development of novel agents to inhibit sodium glucose transporter-2 (SGLT2 ) as a means to better control glucose levels and at the same time augment calorie wasting and lower insulin, blood pressure and uric acid levels. Such actions, indirectly, may also have benefits for the prevention of diabetic complications including renal disease. However, there are also data to support the potential for direct renoprotective actions arising from inhibition of SGLT2, including actions to attenuate diabetes-associated hyperfiltration and tubular hypertrophy, as well as reduce the tubular toxicity of glucose. Some studies have demonstrated significant reductions in albumin excretion in various experimental models, independent of its effects on blood pressure or glucose control. Although promising, such actions remain to be established by comprehensive clinical trials with a renal focus, many of which are currently in progress. This article reviews the clinical and experimental data pertaining to the renal effects of SGLT2 inhibition with a particular focus on dapaglifozin.